The world's repository at 75: a history of the United Nations Archives*. Issue 2 (1st August 2021) - Gelfand, Aleksandr
Abstract : Seventy-five years ago (1945), the United Nations (UN) was founded in San Francisco by 50 nations. There, a small archives unit served to assemble the first records of the organization; this was the first iteration of today's Archives and Records Management Section (ARMS). Throughout its history, the fortunes of the UN Archives have waxed and waned, while its role has continuously evolved. Trying to carve out a place for itself within the largest international organization in the world, its physical and administrative structures have undergone profound changes, as has its mission, number of staff, the type of records it holds and its users. This paper examines significant events in the development of the UN Archives, the challenges it has faced and what may be learned from them.